Facile synthesized Fe nanosheets as superior active catalyst for hydrogen storage in MgH2. (13th August 2019) - Zhang, Liuting; Ji, Liang; Yao, Zhendong; Yan, Nianhua; Sun, Ze; Yang, Xinglin; Zhu, Xinqiao; Hu, Shuanglin; Chen, Lixin
Abstract: Reversible hydrogen storage in MgH2 under mild conditions is a promising way for the realization of "Hydrogen Economy", in which the development of cheap and highly efficient catalysts is the major challenge. Herein, A two-dimensional layered Fe is prepared via a facile wet-chemical ball milling method and has been confirmed to greatly enhance the hydrogen storage performance of MgH2 . Minor addition of 5 wt% Fe nanosheets to MgH2 decreases the onset desorption temperature to 182.1 °C and enables a quick release of 5.44 wt% H2 within 10 min at 300 °C. Besides, the dehydrogenated sample takes up 6 wt% H2 in 10 min under a hydrogen pressure of 3.2 MPa at 200 °C. With the doping of Fe nanosheets, the apparent activation energy of the dehydrogenation reaction for MgH2 is reduced to 40.7 ± 1.0 kJ mol −1 . Further ab initio calculations reveal that the presence of Fe extends the Mg–H bond length and reduces its bond strength. We believe that this work would shed light on designing plain metal for catalysis in the area of hydrogen storage and other energy-related issues. Graphical abstract: The well distributed Fe nanoparticles broken down from nanosheets contributed to the remarkable enhancement in hydrogen storage properties of MgH2 .Image 1 Highlights: Fe nanosheets were successfully prepared by a facile wet-chemical method. Hydrogen could be released at 182.1 °C and absorbed at 75 °C for the composite. The de/hydrogenation activation energy of the composite were significantly reduced. Ab initio calculations revealed that Fe facilitated the breaking of the Mg–H bond.